Shoe collar height effect on athletic performance, ankle joint kinematics and kinetics during unanticipated maximum-effort side-cutting - Lam, G. W. K.; Park, E. J.; Lee, K.-K.; Cheung, J. T.-M. (Journal of Sports Sciences, 2015)
Side-step cutting manoeuvres comprise the coordination between planting and non-planting legs. Increased shoe collar height is expected to influence ankle biomechanics of both legs and possibly respective cutting performance. This study examined the shoe collar height effect on kinematics and kinetics of planting and non-planting legs during an unanticipated side-step cutting. Fifteen university basketball players performed maximum-effort side-step cutting to the left 45° direction or a straight ahead run in response to a random light signal. Seven successful cutting trials were collected for each condition. Athletic performance, ground reaction force, ankle kinematics and kinetics of both legs were analysed using paired t-tests. Results indicated that high-collar shoes resulted in less ankle inversion and external rotation during initial contact for the planting leg. The high-collar shoes also exhibited a smaller ankle range of motion in the sagittal and transverse planes for both legs, respectively. However, no collar effect was found for ankle moments and performance indicators including cutting performance time, ground contact time, propulsion ground reaction forces and impulses. These findings indicated that high-collar shoes altered ankle positioning and restricted ankle joint freedom movements in both legs, while no negative effect was found for athletic cutting performance